Penggambaran Sosok Pendeta Dalam Film The Devil All The Time - Gabriel Jeremy Jeconiah (UNIVERSITAS KALBIS, 2023)
Pastors are representatives of God in the world. A pastor must have a reflection of the attitude and behavior of God. Reflections of God's self such as, humble, kind, serving, and forgiving. In mass communication products such as films, priests are depicted in various ways, such as the figure of a priest in the film The Devil All the Time which is described as different from the figure of a priest in general. The purpose of this study was to determine the depiction of the figure of a priest in the film The Devil All the Time by using the constructivism paradigm. This study uses a qualitative approach and uses the Social Reality Construction Theory and uses Charles Sanders Peirce's semiotic analysis with the triangle of meaning, namely sign, object and interpretant. The results of this study found that there are several depictions of the figure of a priest, namely the figure of the priest in this film is described as a perverted figure, likes to humiliate others, a liar, often denies his actions, is emotional, selfish where the figure of the priest in The Devil All The Time is different. from the figure of a priest in general.